Human Induced Pluripotent Stem Cell Models of Neurodegenerative Disorders for Studying the Biomedical Implications of Autophagy. Issue 8 (3rd April 2020) - Seranova, Elena; Palhegyi, Adina Maria; Verma, Surbhi; Dimova, Simona; Lasry, Rachel; Naama, Moriyah; Sun, Congxin; Barrett, Timothy; Rosenstock, Tatiana Rosado; Kumar, Dhiraj; Cohen, Malkiel A.; Buganim, Yosef; et al.
Abstract: Autophagy is an intracellular degradation process that is essential for cellular survival, tissue homeostasis, and human health. The housekeeping functions of autophagy in mediating the clearance of aggregation-prone proteins and damaged organelles are vital for post-mitotic neurons. Improper functioning of this process contributes to the pathology of myriad human diseases, including neurodegeneration. Impairment in autophagy has been reported in several neurodegenerative diseases where pharmacological induction of autophagy has therapeutic benefits in cellular and transgenic animal models. However, emerging studies suggest that the efficacy of autophagy inducers, as well as the nature of the autophagy defects, may be context-dependent, and therefore, studies in disease-relevant experimental systems may provide more insights for clinical translation to patients. With the advancements in human stem cell technology, it is now possible to establish disease-affected cellular platforms from patients for investigating disease mechanisms and identifying candidate drugs in the appropriate cell types, such as neurons that are otherwise not accessible. Towards this, patient-derived human induced pluripotent stem cells (hiPSCs) have demonstrated considerable promise in constituting a platform for effective disease modeling and drug discovery. Multiple studies have utilized hiPSC models of neurodegenerative diseases to study autophagy and evaluate the therapeutic efficacy of autophagy inducers in neuronal cells. This review provides an overview of the regulation of autophagy, generation of hiPSCs via cellular reprogramming, and neuronal differentiation. It outlines the findings in various neurodegenerative disorders where autophagy has been studied using hiPSC models. Graphical abstract: Image 1 Highlights: Impairment of autophagy causes neurodegeneration. Autophagy inducers exert therapeutic benefits in neurodegenerative disease models. Patient-derived hiPSC models provide relevant cellular platforms for disease modeling and drug discovery. Autophagy has been studied in multiple hiPSC models of neurodegenerative diseases.